Developing Marketing Mechanism of Sustainable Community - Based Tourism Cluster in Nakhon Ratchasima Province - Jaisamrarn, Arnut; Thongdee, Nattinee (Area Based Development Research Journal, 2018)
The objectives of this research are to 1) study situations and problems about marketing mechanism of community-based tourism (CBT), 2) develop marketing mechanism of community-based tourism cluster through participatory action of local community, and 3) increase community-based tourism marketing potential. This research employs qualitative and participatory action research approaches and adopts primary data and field works based on in-depth interview, group discussion and focus group techniques. The key informants are 15 leaders/representatives of the community-based tourism in Nakhon Ratchasima province and 6 leaders/representatives taking part in marketing development research. This research employs content analysis techniques. The study of fifteen community-based tourism villages in Nakhon Ratchasima province reveals marketing management capacity at medium level. Problems in marketing process, which includes product development, and problems in human resources, are found at the lowest level. Furthermore, internal factor analysis indicates the community strengths in its unique, distinctive, and diverse tourism resources. Their weaknesses are identified as the lack of understanding of CBT marketing and lack of CBT cluster networking at provincial level. A model suggested for CBT cluster network plan and marketing mechanism development is “Collaborative and Cooperative” model. The focuses of marketing development are in four aspects: 1) the balanced satisfaction levels between local people and tourists, 2) the effectiveness of community - based tourism marketing management, 3) the mechanism of marketing management of the networked communities, and 4) the strategy of CBT ISAN cluster and human resources networking. The research in developing marketing potential has found that the local community better understand marketing development, especially in tourism program design, marketing channels, and public relations. To strengthen the marketing mechanism management, the CBT Nakhon Ratchasima cluster should consider the five issues of concern: 1) ways for innovation in tourism product design and service, 2) tourism marketing management of CBT, 3) target tourists and ways to reach them, 4) quality and standard services in traditional ways, and 5) ways of marketing promotion.